Effect of oral theophylline on resting energy expenditure in normal volunteers. Issue 11 (November 1994) - Dash, A; Agrawal, A; Venkat, N; Moxham, J; Ponte, J
Abstract : BACKGROUND--The aim of this study was to investigate the contribution of regular treatment with oral theophylline to the increase in resting oxygen consumption observed in patients with chronic airflow limitation who are receiving bronchodilator therapy. METHODS--Resting oxygen consumption (VO2) and carbon dioxide production (VCO2) were measured in 10 normal subjects (six men, age 21-48 years, weight 50-85 kg) before and after 11 days of treatment with either placebo or theophylline in a double blind manner, in twice daily oral doses ensuring trough serum concentrations between 8.4 and 13.5 mg/l. An open canopy method was used to measure VO2 and VCO2 and in all test conditions this was extended for 60 minutes after an inhalation of 800 micrograms of salbutamol super-imposed on the background placebo or theophylline treatment. RESULTS--Resting VO2 and heart rate were increased during theophylline treatment compared with placebo by 6.5% and 8.4% respectively. Salbutamol inhalation transiently increased VO2, VCO2, and heart rate in all tests but this was not modified by background theophylline treatment. CONCLUSION--Oral theophylline treatment causes a sustained increase in resting oxygen consumption and heart rate but does not modify the metabolic response to acutely inhaled salbutamol.